(untitled) (Comprehensive Journal of Science, 2026)
This study examines the role of African preventive diplomacy in settling border disputes among African states, with an analytical application to the Moroccan-Algerian border conflict، The study focuses on the concept of preventive diplomacy, its continental and regional mechanisms, and the role of mediation and negotiations in containing border disputes. It concludes that preventive diplomacy is an important tool for preventing escalation, yet its effectiveness depends on political will, timely intervention, and the strength of follow-up and implementation mechanisms.